The Influence Of Halal Products, Word Of Mouth, and Price on Japanese Restaurant Food Purchasing Decisions - ardhiana ardhiana dwi febrianti; Fira Nurafiani (ASEAN Journal of Halal Study, 2024)
The purpose of this study was determine the effect of Halal Word of Mouth Products and Price on Japanese Restaurant Food Purchasing Decisions. The problem in the study is that there are various Japanese restaurant food products that are still not halal certified, while Japanese restaurants can currently be found easily in the Surabaya area. The purpose of the study was to determine the effect of the influence of Halal Products, Word of Mouth and price on purchasing decisions. The research method used is quantitative with an associative approach. The sample in this study amounted to 121 respondents. Data were collected using a questionnaire and processed using SPSS. The results showed that Halal Products had no effect with a result of 1,199, Word of Mouth of 4,166, and Price of 4,924.